A new species of Lindernia (Linderniaceae) from India - Prasad, Mangavayal Govindan (Phytotaxa, 2014)
A new species, Lindernia tamilnadensis is described and illustrated from Vijayanarayanam, Tirunelveli district of Tamil Nadu, India. The species shows similarity with a worldwide distributed species, Lindernia rotundifolia in its leaf and seed characters but differs mainly in comparatively smaller floral parts, lanceolate calyx lobes, in the absence of trichomes at the base of the anterior corolla lobes, the presence of staminodal appendages, undeflexed fruiting pedicels and globose capsules. Detailed description, illustration and other relevant notes are provided.